Behavior of Visceral Leishmania donovani in an Experimentally Induced T Helper Cell 2 (Th2)-Associated Response Model - Murray, Henry W. (The Rockefeller University Press, 1997)
Although implicated in the clinical expression of human visceral leishmaniasis, a disease-exacerbating T helper cell 2 (Th2)-associated immune response involving interleukin-4 (IL-4) and/ or IL-10 is not readily detectable in experimental visceral infection. To overcome this obstacle to analyzing visceral Leishmania donovani in this relevant immunopathogenetic environment, we sought a model in which a Th2 response induces noncuring infection. Four initial approaches were tested primarily in BALB/c mice which control intracellular L. donovani via an IL-12– and interferon-γ (IFN-γ)–dependent Th1 mechanism: (a) modifying the cytokine milieu when the parasite is first encountered (treatment with exogenous IL-4 or anti–IL-12), (b) providing sustained endogenous exposure to a Th2 cytokine (infection of IL-4 transgenic mice), (c) increasing the parasite challenge inoculum, and (d) injecting heat-killed L. major promastigotes (HKLMP) to induce a cross-reactive Th2 response to live L. donovani. Only the last approach generated a functional Th2-type response that induced disease exacerbation accompanied by inhibition of tissue granuloma assembly. In HKLMP-primed BALB/c mice, prophylaxis with anti–IL-4, anti–IL-10, or exogenous IL-12 (but not IFN-γ) readily restored resistance. In primed mice with established visceral infection, treatment with either IL-12 or IFN-γ also successfully induced antileishmanial activity. The results in this model (a) suggest that rather than acting alone, IL-4 and IL-10 may act in concert to prevent acquisition of resistance to L. donovani, (b) reemphasize the capacity of IL-12 to reverse early Th2-related effects, and (c) demonstrate that Th1 cytokines (IL-12, IFN-γ) have therapeutic action in an established systemic infection despite the presence of a disease-exacerbating Th2-type response.